Exercise interventions for patients with pediatric cancer during inpatient acute care: A systematic review of literature. Issue 11 (19th April 2017) - Rustler, Vanessa; Hagerty, Meaghan; Daeggelmann, Julia; Marjerrison, Stacey; Bloch, Wilhelm; Baumann, Freerk T.
Abstract: Physical inactivity has been shown to exacerbate negative side effects experienced by pediatric patients undergoing cancer therapy. Exercise interventions are being created in response. This review summarizes current exercise intervention data in the inpatient pediatric oncology setting. Two independent reviewers collected literature from three databases, and analyzed data following the PRISMA statement for systematic reviews and meta‐analyses. Ten studies were included, representing 204 patients. Good adherence, positive trends in health status, and no adverse events were noted. Common strategies included individual, supervised, combination training with adaptability to meet fluctuating patient abilities. We recommend that general physical activity programming be offered to pediatric oncology inpatients.